Innate Lymphoid Cells in the Central Nervous System - Wang, Shuaiwei; van de Pavert, Serge A. (Frontiers in Immunology, 2022)
Immune cells are present within the central nervous system and play important roles in neurological inflammation and disease. As relatively new described immune cell population, Innate Lymphoid Cells are now increasingly recognized within the central nervous system and associated diseases. Innate Lymphoid Cells are generally regarded as tissue resident and early responders, while conversely within the central nervous system at steady-state their presence is limited. This review will describe the current understandings on Innate Lymphoid Cells in the central nervous system at steady-state and its borders plus their involvement in major neurological diseases like ischemic stroke, Alzheimer’s disease and Multiple Sclerosis.